The talismans of Shannara - Brooks, Terry (New York : Ballantine, 1994)
Leader of the Shadowen, Rimmer Dall, sends his four Horsemen against Walker Boh and the scions of Shannara.
"A Del Rey book.".
Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Young Adult
Keywords: Elves -- Fiction; Shannara (Imaginary place) -- Fiction; Fairies -- Fiction; Shannara (Imaginary place) -- Fiction; Fantastic fiction